Hardness Effect Of DLC On Tribological Properties For Sliding Bearing Under Boundary Lubrication Condition In Additive-Free Mineral Base Oil - Masripan, Nor Azmmi; Ohara , Kenji; Umehara, Noritsugu; Kousaka, Hiroyuki; Tokoroyama, Takayuki; Inami, Shigeru; Zushi, Koji; Fujita, Masahito (Elsevier, 2013)
Diamond-like carbons (DLC) with different hardness of 47.1, 11.8 and 6.05 GPa were coated on SUJ2 rollers, and their tribological properties were investigated under boundary lubrication conditions in an additive-free mineral base oil at different testing oil temperatures of 24, 80 and 160 °C. The hardest DLC with 47.1 GPa showed the lowest friction coefficient and wear. From the results of the Raman analyses and spectroscopy ellipsometry, we found that the structure changed at oil temperature of thickness of 80 °C with the formation of a thick layer of 160 nm at the topmost sliding contact surface which provided the lowest friction coefficient of 0.03 in an additive-free mineral base oil.